Novel high performance hollow fiber ultrafiltration membranes spun from LiBr doped solutions - Idris, A.; Ahmed, I.; Misran, M. (2009)
The objective of this research is to evaluate the performance of the polyethersulfone (PES) hollow fiber ultrafiltration membranes spun from LiBr doped solutions prepared using the newly developed microwave heating technique. In addition the resultant hollow fiber membranes were introduced to a new post-treatment method where the membranes were placed in water and irradiated using the microwave technique. Various concentrations of the additive, LiBr, (1-4 wt.) were added into the PES dope solutions. The dissolution of PES and LiBr in DMF was facilitated by the microwave heating technique. The performance of the membranes was evaluated in terms of pure water permeation and polyethylene glycol separation and its molecular weight cutoff (MWCO) was determined. The results revealed that the microwave post-treatment technique was proven to be effective in producing higher performance membranes. The best performance was obtained at 3 LiBr with MWCO at 90 rejection in the range of 2.83 kDa and high flux range of 222.18 (Lm- 2 h- 1 bar- 1). LiBr interacts in the membrane matrix resulting in the enhancement of the hydrophilic property of the membrane and this is confirmed by the contact angle measurement.